Cohort profile: the Halland osteoarthritis (HALLOA) cohort–from knee pain to osteoarthritis: a longitudinal observational study in Sweden - Ann Bremander; Maria L E Andersson; S Bergman; Katarina Aili; Emma Haglund (BMJ Open)
Purpose The overall objective in this study is to investigate the early development of radiographic knee osteoarthritis (OA) and its association with hand or/and knee OA, metabolic diseases, biomarkers, chronic pain, physical function and daily physical activity types.Participants The Halland osteoarthritis (HALLOA) cohort is a longitudinal cohort study that includes individuals with knee pain in the southwest of Sweden. Enrolment took place from 2017 to 2019. The inclusion criteria were current knee pain, with no former known radiographic knee OA and no cruciate ligament rupture or rheumatological disorder. The participants were recruited: (1) when seeking care for knee pain in primary healthcare or (2) by advertisements in local newspapers. There are 306 individuals included in the study, mean age (SD) 51.7 (8.7) years and 69% are women. The baseline and follow-ups include clinical tests, radiographical examinations, blood samples, metabolic measures, pain pressure thresholds, tests of physical functions, daily physical activity types and patient-reported outcomes.Findings to date There were associations between metabolic factors and radiographic knee OA, even in those with normal body mass index at baseline. In addition, clinical hand OA was positively associated with fasting plasma glucose. We also found that modifiable factors as increased visceral fat and total body fat were associated with increased pain sensitivity among individuals with knee pain.Future plans By studying possible pathophysiological mechanisms of OA over time, we aim to provide new insights on OA progression, identify usable preventive measures helping the clinicians in the management of the disease and improve health for the patients. It is also important to study the development of chronic pain in OA, to get tools to identify individuals at risk and to be able to offer them treatment.Trial registration number ClinicalTrials.gov (NCT04928170).